2021
DOI: 10.1111/jfpp.15423
|View full text |Cite
|
Sign up to set email alerts
|

Production of synbiotic ice cream using Lactobacillus casei / Lactobacillus plantarum and fructooligosaccharides

Abstract: Production of synbiotic ice creams formulated with fructooligosaccharides was performed in this study. Fermentation of ice cream mix was carried out using Lactobacillus casei and Lactobacillus plantarum. Fermented samples had lower pH and higher acidity than unfermented samples. The highest viability of probiotics during storage was associated with synbiotic ice creams, demonstrating a beneficial role of fructooligosaccharides for the growth of lactic acid bacteria (LAB). The highest degree of hydroly-How to c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 36 publications
0
15
1
Order By: Relevance
“…stated that the titratable acidity of probiotic ice cream increased with increasing the prebiotic compound, such as inulin and fructooligosaccharides. However, Sabet‐Sarvestani et al 46 . reported that the addition of prebiotic did not change the pH and acidity of symbiotic ice creams formulated with fructooligosaccharides and Lactobacillus casei / Lactobacillus plantarum .…”
Section: Resultsmentioning
confidence: 98%
See 2 more Smart Citations
“…stated that the titratable acidity of probiotic ice cream increased with increasing the prebiotic compound, such as inulin and fructooligosaccharides. However, Sabet‐Sarvestani et al 46 . reported that the addition of prebiotic did not change the pH and acidity of symbiotic ice creams formulated with fructooligosaccharides and Lactobacillus casei / Lactobacillus plantarum .…”
Section: Resultsmentioning
confidence: 98%
“…reported that hardness increased during the storage for 180 days of probiotic ice cream samples that had been supplemented with apple, orange, oat and wheat fiber. In general, fibers enhance the hardness of samples by absorbing water molecules and forming chemical bonds within molecular structures 46 …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Synbiotic ice cream received the highest overall acceptance scores. Sabet-Sarvestani et al [ 20 ] produced synbiotic ice cream using Lactobacillus casei/Lactobacillus plantarum and fructooligosaccharides, and they observed a beneficial role of these prebiotics for the growth of probiotics. Kowalczyk et al [ 34 ] observed that the survival of Bifidobacterium animalis ssp.…”
Section: Resultsmentioning
confidence: 99%
“…The production of frozen yoghurts or ice creams with low fat or lactose levels and/or with added prebiotics and probiotics created new opportunities for the development of dairy foods with health-promoting properties. An increasing number of papers describe the formulations and characteristics of such products [ 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 ]. The production of ovine’s and caprine’s yoghurts and frozen yoghurts has also followed this trend.…”
Section: Introductionmentioning
confidence: 99%